Agama, Tradisi Budaya dan Peradaban - Abdul Gafur; Risan Rusli; Anisatul Mardiyah; Anica Anica; Mungafif Mungafif (Fakultas Adab dan Humaniora UIN Raden Fatah, 2021)
This paper focuses on what religion is, cultural traditions and civilization and their relationship and obstacles in civilization. Religion as a teaching revealed by God as a guide for humans for the continuation of their life. Religion is also a regulatory norm for its adherents which in daily life is indispensable for sustainability in the future. Because without religion, their life will be chaotic, especially if social activities or social traditions are very complex, this is very much needed. Tradition is a habit that has been carried out from the past, this is done so that the tradition is maintained from one successor to another, while civilization is an end result that is done by humans themselves, both materially and immaterially. This study is a literature review with qualitative descriptive data using content analysis, which produces data that there is a very close relationship between religion, cultural traditions and civilization. Religion is very closely related to traditional culture itself because in culture there are elements, one of which is religion. Likewise, civilization is also closely related to religion because one aspect of human life will not be separated from the rules (religion) itself. Because civilization is the result of the creation of cultured humans themselves.